Dimensional changes of CAD/CAM polymer crowns after water aging – An in vitro experiment. (April 2022) - Schepke, U.; Filius, D.; Lohbauer, U.; la Bastide-van Gemert, S.; Gresnigt, M.M.M.; Cune, M.S.
Abstract: Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM) polymers can potentially replace traditional materials used for manufacturing indirect restorations. In 2012, Lava Ultimate (LU) was introduced as a highly suitable material for implant-supported single crowns. Three years after its introduction, the manufacturer issued a change in indication for the material, implying that they no longer considered the material to be suitable for crown indications due to debonding issues. A clinical trial with implant-borne Lava Ultimate crowns bonded to zirconia abutments revealed that 80 percent of the LU crowns showed debonding from the abutment within one year, whereas no debonding occurred when an alternative full-ceramic restoration material was used. These results suggest that the material itself had been the cause of the debonding. However, the exact reason for the debonding remained unclear. Water uptake in resin methacrylates like LU is known to cause dimensional changes resulting in mechanical stress on the RelyX Ultimate (RU) cement. The purpose of this study is to quantify the dimensional changes in LU caused by water uptake and relate these dimensional changes to the failure of the RU cement. Twenty-five identical LU-crowns were divided into three groups. 10 LU-crowns with abutment and 10 crowns without abutments were stored in water for 23 days and were only removed for measurement. Five crowns served as a control to calibrate the measurements. The internal diameter was measured eight times with a TS 460 Heidenhain touch probe. For visualization purposes, one crown was also 3D scanned before and after water treatment. The results showed that after 23 days in water the mean increase in diameter for the groups with and without abutment was 36.6 μm (SD = 35, 1) and 36.7 μm (SD = 26, 5) respectively. Mixed effects modelling indicated no significant between-group differences at any time point. Exposure of LU to water results in dimensional changes causing mechanical stress on the crown-abutment complex. It can be estimated that RU cement fails after an expansion of more than 4 μm. Within the limitations of this in vitro study, it can be concluded that the dimensional changes induced by water uptake can cause debonding issues. As more CAD/CAM polymers for restorative purposes are expected to be developed, the results of this study should stimulate manufacturers to quantify their products' dimensional changes in a wet environment before market release. Graphical abstract: Image 1